2001
DOI: 10.1096/fj.00-0798com
|View full text |Cite
|
Sign up to set email alerts
|

ATP binding cassette transporter ABCA1 modulates the secretion of apolipoprotein E from human monocyte‐derived macrophages

Abstract: Apolipoprotein E (apoE) produced by macrophages in the arterial wall protects against atherosclerosis, but the regulation of its secretion by these cells is poorly understood. Here we investigated the contribution of the adenosine triphosphate binding cassette transporters ABCA1 and ABC8 to the secretion of apoE from either primary human monocyte-derived macrophages (HMDM) or human THP1 macrophages. During incubations of up to 6 h, apoE secretion from both THP1 macrophages and HMDM was stimulated by 8-Br-cAMP,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
61
1
1

Year Published

2001
2001
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(70 citation statements)
references
References 49 publications
7
61
1
1
Order By: Relevance
“…One of them is to induce the expression of apoE (38). Data from this report clearly demonstrated that apoE increases ABCA1 expression via a mechanism involving VLDLR/apoER2.…”
Section: Discussionmentioning
confidence: 59%
“…One of them is to induce the expression of apoE (38). Data from this report clearly demonstrated that apoE increases ABCA1 expression via a mechanism involving VLDLR/apoER2.…”
Section: Discussionmentioning
confidence: 59%
“…Reconstituting these cells with ECM prompted a dramatic increase in cholesterol efflux to apoA-I. The reconstituted efflux was sensitive to glyburide, an inhibitor of ABCA1 function (57)(58)(59)(60), suggesting that the ECM binding to apoA-I and ABCA1 activity function together to promote lipid efflux to apoA-I. In a similar manner, U937 macrophages, which express ABCA1 and lack an active ECM binding site, do not efflux cholesterol to apoA-I (Fig.…”
Section: Discussionmentioning
confidence: 85%
“…5). This may suggest that an increase of the lipid release mediated by endogenous apoE is also mediated by ABCA1 (32).…”
Section: Discussionmentioning
confidence: 99%